2008
DOI: 10.1088/1751-8113/41/17/175204
|View full text |Cite
|
Sign up to set email alerts
|

Variational calculus with constraints on general algebroids

Abstract: Variational calculus on a vector bundle E equipped with a structure of a general algebroid is developed, together with the corresponding analogs of Euler-Lagrange equations. Constrained systems are introduced in the variational and in the geometrical setting. The constrained EulerLagrange equations are derived for analogs of holonomic, vakonomic and nonholonomic constraints. This general model covers majority of first-order Lagrangian systems which are present in the literature and reduces to the standard vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(155 citation statements)
references
References 40 publications
2
153
0
Order By: Relevance
“…We note that the idea of applying implicit differential equations to nonholonomic systems is found in an earlier work by Ibort et al, 32 see also Grabowska and Grabowski 33 for a generalization to vector bundles with algebroid structures.…”
Section: Lagrange-dirac Systemsmentioning
confidence: 80%
“…We note that the idea of applying implicit differential equations to nonholonomic systems is found in an earlier work by Ibort et al, 32 see also Grabowska and Grabowski 33 for a generalization to vector bundles with algebroid structures.…”
Section: Lagrange-dirac Systemsmentioning
confidence: 80%
“…The notation is borrowed from [19,21,42] and we refer to these papers for details. In particular, we use affine coordinates (x a , ξ i ) on E * and the dual coordinates (x a , y i ) on E, associated with dual local bases, (e i ) and (e i ), of sections of E and E * , respectively.…”
Section: Skew Algebroidsmentioning
confidence: 99%
“…[9,75,76]). In [19,21], in turn, has been observed that its geometric background is actually based on double vector bundle morphisms ε and the Jacobi identity plays no role in the construction of dynamics, that gives a space for further generalizations.…”
Section: Lagrangian Formalism For General Algebroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same Lie algebroid setting, other authors [16] consider variational constrained mechanical systems. In another direction, a unified approach of nonholonomic and vakonomic mechanics, using general algebroids instead of just Lie algebroids, was developed in [9].…”
Section: Introductionmentioning
confidence: 99%